Exploring the Individual, Socioeconomic and Contextual Determinants Associated with Daily Tobacco Consumption in Portugal - Laura Almeida; Carla Teotónio; Micaela Antunes (Notas Económicas)
The National Program for Tobacco Prevention and Control reflects awareness of tobacco as a major public health problem in Portugal. To infer which population groups should be targeted, we estimate sex-specific logistic regressions to analyze the determinants of daily tobacco consumption, using the most recent microeconomic data from the Portuguese Health Interview Survey. To assess the existence of inequalities, we calculate concentration indices, ranking individuals by income and education. Nine percent of women and twenty percent of men smoke on a daily basis, with drinking, depression and living in Azores significantly increasing the risk. Secondary (upper) education increases the odds of daily smoking for women and decreases the odds for men. Unemployment increases the odds for men only and depression puts women at significantly higher risk. The results highlight the importance of not only adopting cross-cutting policies to reduce tobacco consumption, but also targeting the most vulnerable to mitigate existing income- and schooling-related health inequity.